Tailoring a Minimal Self‐Replicate DNA Circuit for Highly Efficient Intracellular Imaging of microRNA. Issue 17 (30th January 2023) - Wei, Jie; Yu, Mengdi; Tan, Kaiyue; Shang, Jinhua; He, Shizhen; Xie, Chenxia; Liu, Xiaoqing; Wang, Fuan
Abstract: Trace analyte detection in complex intracellular environment requires the development of simple yet robust self‐sufficient molecular circuits with high signal‐gain and anti‐interference features. Herein, a minimal non‐enzymatic self‐replicate DNA circuitry (SDC) system is proposed with high‐signal‐gain for highly efficient biosensing in living cells. It is facilely engineered through the self‐stacking of only one elementary cascade hybridization reaction (CHR), thus is encoding with more economic yet effective amplification pathways and reactants. Trigger (T ) stimulates the activation of CHR for producing numerous T replica that reversely motivate new CHR reaction cycles, thus achieving the successive self‐replication of CHR system with an exponentially magnified readout signal. The intrinsic self‐replicate circuity design and the self‐accelerated reaction format of SDC system is experimentally demonstrated and theoretically simulated. With simple circuitry configuration and low reactant complexity, the SDC amplifier enables the high‐contrast and accurate visualization of microRNA (miRNA), ascribing to its robust molecular recognition and self‐sufficient signal amplification, thus offering a promising strategy for monitoring these clinically significant analytes. Abstract : An enzyme‐free self‐replicate DNA circuitry (SDC) system is engineered for microRNA (miRNA) imaging. Trigger‐activated cascade hybridization reaction (CHR) leads to the formation of dsDNA copolymers carrying numerous reconstituted triggers for reversely stimulating CHR, thus yielding hyperbranched DNA products with an exponentially magnified fluorescence signal.